DASAR EPISTEMOLOGI DALAM FILSAFAT PENDIDIKAN ISLAM - Abidin Nurdin; Sri Astuti A. Samad; Munawwarah A. Samad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Epistemology is the study of the source of knowledge or theories about science. Islamic epistemology views everything in a holistic manner that is not separate between aspects of the world and the hereafter, besides containing worldly values but also contains aspects of the afterlife. Epistemologically, knowledge in Islam is based on two things; first, through rational knowledge; secondly, through religious knowledge and experience, first is knowledge about beings and second is Divine reality. Therefore, in the philosophy of Islamic education, the source of knowledge is revelation over reason and the five senses. Revelation as the source of knowledge is what gives certainty to human reason about truth. Crisis of morality or human behavior is now an important factor occupying the epistemology base of true Islamic education, because education that is only able to educate intellectually and good skills is clearly considered a failure without being decorated with noble character.